Abiotic and biotic drivers of fatty acid tracers in ecology: A global analysis of chondrichthyan profiles. (21st April 2019) - Meyer, Lauren; Pethybridge, Heidi; Nichols, Peter D.; Beckmann, Crystal; Huveneers, Charlie
Abstract: The use of fatty acid (FA) tracers is a growing tool in trophic ecology, yet FA profiles are driven by a number of abiotic and biotic parameters, making interpretation and appropriate use confusing for ecologists. We undertook a global analysis, compiling FA profiles of 106 chondrichthyan (shark, ray and chimaera) populations, as a model to test the utility of FA profiles to partition a priori trophic guilds, phylogeny, water temperature and habitats. Individual FAs characterizing these four factors were identified, promoting the use of these FAs as ecological tracers across taxa. Habitat type was linked to five FAs: 16:0, 18:0 and biologically essential 22:6ω3 (indicative of the deep sea), 20:5ω3 (non‐complex demersal and deep‐sea demersal) and 20:4ω6 (reef and brackish water). Temperature was a key driver of four FAs (22:5ω6, 22:4ω6, 20:1ω9 and 20:5ω3), while trophic guild and phylogeny were important drivers of two pairs of FA tracers (18:0 and 20:5ω3; 20:1ω9 and 18:1ω9, respectively). This analysis provides a novel understanding of the biological and ecological information that can be inferred from FA profiles and further validates the use of FAs as tracers to investigate the trophic ecology of chondrichthyans. Future research should prioritize ex situ studies to further disentangle the influence of factors across taxa and tissue types, quantify biomodification, enabling the use of quantitative methods for diet determination and further develop 'FATscapes' to elucidate fine‐scale trophic geography and climate variability. Additionally, the creation of a taxonomically inclusive FA data repository will enable further meta‐analyses. A plain language summary is available for this article. Abstract : Plain Language Summary